Effects of a selective androgen receptor modulator (SARM), GSK2849466A, on stress urinary incontinence and bladder activity in rats with ovariectomy‐induced oestrogen deficiency. (20th March 2020) - Kadekawa, Katsumi; Kawamorita, Naoki; Shimizu, Takahiro; Kurobe, Masahiro; Turnbull, Philip S.; Chandra, Sundeep; Kambara, Takahito; Barton, Joanna C.; Russell, Alan J.; Yoshimura, Naoki
Abstract : Objectives: To report the effect of a selective androgen receptor modulators (SARMs) on the urethral continence mechanisms in a rat model of stress urinary incontinence (SUI) induced by bilateral ovariectomy (OVX). Materials and methods: Female Sprague‐Dawley rats with bilateral OVX were used. Rats were divided into five groups; sham operated, vehicle‐treated OVX, low‐dose SARM‐treated OVX (GSK2849466A: 0.005 mg/kg/day, per os [p.o.]), high‐dose SARM‐treated OVX (GSK2849466A: 0.03 mg/kg/day, p.o.) and dihydrotestosterone (DHT)‐treated OVX (1 mg/kg/day, subcutaneous) groups. After 4 weeks of SARM treatments or 3 weeks of DHT treatment (6 weeks after OVX), rats were subjected to evaluation of the sneeze‐induced continence reflex using microtransducer‐tipped catheter methods, sneeze‐induced leak‐point pressure, and continuous cystometry measurements, followed by histological analyses of urethral tissues. Results: (i) OVX significantly impaired urethral continence function after 6 weeks to induce SUI during sneezing. (ii) Low‐dose SARM treatment restored urethral baseline pressure (UBP) without affecting the amplitude of urethral response during sneezing (A‐URS), partially reversing OVX‐induced SUI during sneezing. (iii) High‐dose SARM treatment reversed decreases in both UBP and A‐URS, more effectively preventing SUI during sneezing. (iv) DHT treatment only restored A‐URS without affecting UBP, partially preventing OVX‐induced SUI during sneezing. (v) The high‐dose SARM treatment induced hypertrophy of the striated and smooth muscle around the urethra. (vi) SARM treatment did not affect bladder function in sham or OVX rats. Conclusion: Treatment with SARMs could be a more effective modality for the treatment of SUI than DHT, without affecting bladder function, by enhancing smooth‐ and striated muscle‐mediated urethral function under stress conditions such as sneezing.